An equation is a statement which says two expressions are equal. An algebraic expression may refer a set of constants, variables and operators with or without combinations. Algebraic simplifier is a common terminology for various methods of simplifying an algebraic expression. The idea of simplifying an algebraic expression is making it in more presentable form. Algebraic expression simplifier edit and transform the word statement to mathematical statement.

An algebraic expression is a mathematical model of a verbal statement.

## Simplify any Algebraic Expression

Algebraic expression can be transformed into another expression without change in the evaluation of the expressions. The process of such transformations is called simplification of algebraic expression or solving algebraic expression. Algebraic simplification also includes editing and proper transformation of the word statement to mathematical statement. In word problems, there may be certain sentences which may not be necessary to consider for finding a mathematical solution. Sometimes equation may not look solvable at the first instant because
the expressions on both sides of the equation may not be in a simplified
form. Algebraic expression simplifier helps you to simplify those expressions by using proper strategy, the solution may be very easy.

##
Solved Examples

**Question 1: **Find the value of ‘x’, if 2

^{x} = 8.

** Solution: **
Given 2^{x} = 8

Step 1:

Factors of 8 = 2 x 2 x 2 = 2^{3}

Step 2:

Recall the algebraic expression simplifier for 8 as 2^{3}

and take the strategy of using exponential laws,

=> 2^{x} = 8

=> 2^{x} = 2^{3} [If x^{m} = x^{n} then m = n ]

=> x = 3

**Answer: **The value of x is 3.

**Question 2: **Simplify the algebraic expression $\frac{x^2 – 9}{x – 3}$

** Solution: **
Given $\frac{x ^ 2 – 9}{x – 3}$

Step 1:

Factorization of the numerator

x^{2} - 9 = x^{2} - 3^{2} = (x - 3)(x + 3)

[ a^{2} - b^{2} = ((a - b)(a + b) ]

**Step 2:**

=> $\frac{x ^2 – 9}{x – 3}$ = $\frac{(x - 3)(x + 3)}{x – 3}$

= x + 3

Cancelling the common factor (x – 3) under some assumption that x ≠ 3.

=> $\frac{x ^2 – 9}{x – 3}$ = x + 3.

**Question 3: **Charles is two times as the age of Jacson. Marcus is five year older
than Jacson's age. Together their ages add up to 61. How old is Marcus.

** Solution: **
**Step 1:**

Let the age of Jacson = x years

Then Charles age = 2x

and Marcus age = x + 5

Step 2:

Sum of their ages = 61

=> x + 2x + x + 5 = 61

=> 4x + 5 = 61

Subtract 5 from both sides

=> 4x + 5 - 5 = 61 - 5

=> 4x = 56

Divide each side by 4

=> $\frac{4x}{4} = \frac{56}{4}$

=> x = 14, Jacson age

Step 3:

Charles age = 2x = 2 * 14 = 28

and Marcus age = x + 5 = 14 + 5 = 19

Hence Jacson is 14, Charles is 28 and Marcus is 19.